x+6y-9x-13y+2x=

Simple and best practice solution for x+6y-9x-13y+2x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+6y-9x-13y+2x= equation:


Simplifying
x + 6y + -9x + -13y + 2x = 0

Reorder the terms:
x + -9x + 2x + 6y + -13y = 0

Combine like terms: x + -9x = -8x
-8x + 2x + 6y + -13y = 0

Combine like terms: -8x + 2x = -6x
-6x + 6y + -13y = 0

Combine like terms: 6y + -13y = -7y
-6x + -7y = 0

Solving
-6x + -7y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7y' to each side of the equation.
-6x + -7y + 7y = 0 + 7y

Combine like terms: -7y + 7y = 0
-6x + 0 = 0 + 7y
-6x = 0 + 7y
Remove the zero:
-6x = 7y

Divide each side by '-6'.
x = -1.166666667y

Simplifying
x = -1.166666667y

See similar equations:

| -9h+12=-24 | | -1=n-4 | | 12y=21/4 | | 9(2x-6)=3(6x+1) | | 7(5+c)=6(c-1) | | -17+3y=51 | | (8f)/(6f) | | 8f/6f | | 6y-6=3y+9 | | n/2=12 | | 14+-8t=1328 | | 4(x+9)-4whenx=3 | | 9x+8=-64 | | -25-4c=17 | | -3p+7=5(12p+6) | | 7q/7=84 | | 5x+8(1/3x+8)=-5 | | K-8-1=3+4k+k | | 3+8x=63 | | 7+3m-2=8m+11-4m | | 8t+16=3t-6t+8t-34 | | 1/7(x+7)=1/14(2x+14) | | a/6=20 | | 2/3y-1/6y+4=18 | | 3-4n=-12-7n | | 5n/10=25 | | 13=3w-5 | | 6b+3=7+2b | | 5/6k=7/18 | | x/14-5x+2/49=3x-4/7 | | 8(8-7a)=176 | | 1/n=3/9 |

Equations solver categories